2015
DOI: 10.1016/j.ccell.2015.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Strategies for Treating Brain Metastases from Breast Cancer

Abstract: Summary Brain metastasis is an end stage in breast cancer progression. Traditional treatment options have minimal efficacy, and overall survival is on the order of months. The incidence of brain metastatic disease is increasing with the improved management of systemic disease and prolongation of survival. Unfortunately, the targeted therapies that control systemic disease have diminished efficacy against brain lesions. There are reasons to be optimistic, however, as emerging therapies have shown promise in pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
125
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(129 citation statements)
references
References 96 publications
(99 reference statements)
2
125
0
2
Order By: Relevance
“…The knockdown efficiency of NP-siRNAs was confirmed by RNAscope staining of brain metastatic mouse tissues (Supplemental Figure 4, H and I). By week 4, NP-Lnc-BM siRNAs had significantly reduced brain metastatic burden compared with the control siRNA or PBS ( Figure 3, B and C); however, metastatic lesions of other regions were not affected (Supplemental Figure 4, to the brain by limiting the delivery of many currently available therapeutic agents to the brain metastatic lesions (6). Previous research works have indicated that chitosan nanoparticles (NPs) can efficiently transport BBB-impermeable siRNAs to the brain (20), which may be valuable in targeting BCBM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The knockdown efficiency of NP-siRNAs was confirmed by RNAscope staining of brain metastatic mouse tissues (Supplemental Figure 4, H and I). By week 4, NP-Lnc-BM siRNAs had significantly reduced brain metastatic burden compared with the control siRNA or PBS ( Figure 3, B and C); however, metastatic lesions of other regions were not affected (Supplemental Figure 4, to the brain by limiting the delivery of many currently available therapeutic agents to the brain metastatic lesions (6). Previous research works have indicated that chitosan nanoparticles (NPs) can efficiently transport BBB-impermeable siRNAs to the brain (20), which may be valuable in targeting BCBM.…”
Section: Resultsmentioning
confidence: 99%
“…Clinically, patients with either the HER2-positive or the triple-negative type of breast cancer have significantly higher incidences of brain metastasis, ranging between 20% and 50% (3,4). Although modern multidisciplinary care has been applied to treat cases of brain metastasis (5), the benefit of these treatments is limited by their palliative and localized tendencies (6). Therefore, there is an imperative need for the development of novel therapies based on the biological and molecular mechanisms of brain metastatic lesions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, TGF-β released from colorectal cancer cells stimulated CAFs to secrete IL-11, which feeds back to tumor cells to activate STAT3 signaling, favoring the survival of metastatic cells in the liver (Calon et al 2012). In the brain stroma, reactive astrocytes also mediate important cross-talks with MICs to enhance their proliferation, survival, and metastasis (Kodack et al 2015). Astrocytes promote stem cell-like traits to breast cancer cells by activating Notch signaling in the brain ( Fig.…”
Section: Co-option Of the Metastatic Nichementioning
confidence: 99%
“…Numerous strategies have been proposed to improve the clinical management of BC patients with metastatic brain disease, including prevention; better risk prediction and diagnosis of small, more manageable BM using molecular imaging; targeted drug delivery vectors, like nanoparticles; application of targeted agents to the neurosurgical cavity and externally activating sites of bioavailability to targeted drug conjugates (e.g., ultrasound BBB permeabilisation). Taking the Hydra analogy further, one idea gaining more support in the biomedical community is simultaneous targeting of tumour cell abnormalities and features of the neural niche on which growth and drug resistance depend [77,140,141]. Multiple studies have now verified the role of the metastatic brain tumour microenvironment in driving adaptation, outgrowth and drug resistance [29,54,57,[65][66][67]116].…”
Section: Future Directions and Final Commentsmentioning
confidence: 99%